Conditionality in the context of housing‐led homelessness policy: Comparing Australia's Housing First agenda to Scotland's "rights‐based" approach. Issue 1 (26th December 2019) - Clarke, Andrew; Watts, Beth; Parsell, Cameron
Abstract: Homelessness services and policy have historically tended to be organised by an explicitly conditional logic, wherein people experiencing homelessness must prove their "housing readiness" before accessing settled housing. This model has been robustly challenged in recent decades by "housing‐led" approaches that ostensibly eschew conditionality and prioritise the rapid rehousing of people experiencing homelessness. Various countries now include housing‐led approaches in the national policy frameworks, including Australia, which overhauled its approach to homelessness in 2008, and Scotland, where a housing‐led approach is supported by a legal right to housing for homeless households. Notwithstanding this policy shift, conditionality remains an enduring feature of responses to homelessness in both jurisdictions. This paper sheds light on this phenomenon by comparing the Australian experience with that of Scotland. We demonstrate how conditionality remains a feature of both jurisdictions; however, there is greater effort in Scotland to identify and minimise conditionality, whereas in Australia it is able to persist relatively unchallenged. We conclude with some reflections on what Australia can learn from Scotland's relative success, highlighting the importance of a national‐level policy framework and an adequate affordable housing supply.